The Hitchhiker Guide to CD4+ T-Cell Depletion in Lentiviral Infection. A Critical Review of the Dynamics of the CD4+ T Cells in SIV and HIV Infection - Le Hingrat, Quentin; Sereti, Irini; Landay, Alan L.; Pandrea, Ivona; Apetrei, Cristian (Frontiers in Immunology, 2021)
CD4+ T-cell depletion is pathognomonic for AIDS in both HIV and simian immunodeficiency virus (SIV) infections. It occurs early, is massive at mucosal sites, and is not entirely reverted by antiretroviral therapy (ART), particularly if initiated when T-cell functions are compromised. HIV/SIV infect and kill activated CCR5-expressing memory and effector CD4+ T-cells from the intestinal lamina propria. Acute CD4+ T-cell depletion is substantial in progressive, nonprogressive and controlled infections. Clinical outcome is predicted by the mucosal CD4+ T-cell recovery during chronic infection, with no recovery occurring in rapid progressors, and partial, transient recovery, the degree of which depends on the virus control, in normal and long-term progressors. The nonprogressive infection of African nonhuman primate SIV hosts is characterized by partial mucosal CD4+ T-cell restoration, despite high viral replication. Complete, albeit very slow, recovery of mucosal CD4+ T-cells occurs in controllers. Early ART does not prevent acute mucosal CD4+ T-cell depletion, yet it greatly improves their restoration, sometimes to preinfection levels. Comparative studies of the different models of SIV infection support a critical role of immune activation/inflammation (IA/INFL), in addition to viral replication, in CD4+ T-cell depletion, with immune restoration occurring only when these parameters are kept at bay. CD4+ T-cell depletion is persistent, and the recovery is very slow, even when both the virus and IA/INFL are completely controlled. Nevertheless, partial mucosal CD4+ T-cell recovery is sufficient for a healthy life in natural hosts. Cell death and loss of CD4+ T-cell subsets critical for gut health contribute to mucosal inflammation and enteropathy, which weaken the mucosal barrier, leading to microbial translocation, a major driver of IA/INFL. In turn, IA/INFL trigger CD4+ T-cells to become either viral targets or apoptotic, fueling their loss. CD4+ T-cell depletion also drives opportunistic infections, cancers, and comorbidities. It is thus critical to preserve CD4+ T cells (through early ART) during HIV/SIV infection. Even in early-treated subjects, residual IA/INFL can persist, preventing/delaying CD4+ T-cell restoration. New therapeutic strategies limiting mucosal pathology, microbial translocation and IA/INFL, to improve CD4+ T-cell recovery and the overall HIV prognosis are needed, and SIV models are extensively used to this goal.